The Bone Black Pigment Identification by Noninvasive, In Situ Infrared Reflection Spectroscopy - Alessia Daveri; Marco Malagodi; Manuela Vagnini (Journal of Analytical Methods in Chemistry)
Two real case studies, an oil painting on woven paper and a cycle of mural paintings, have been presented to validate the use of infrared reflection spectroscopy as suitable technique for the identification of bone black pigment. By the use of the sharp weak band at 2013 cm−1, it has been possible to distinguish animal carbon-based blacks by a noninvasive method. Finally, an attempt for an eventual assignment for the widely used sharp band at 2013 cm−1 is discussed.